Hubungan Masa Kerja Dengan Stres Kerja PadaPustakawan Perpustakaan Universitas Gadjaii Mada Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak.Ilmu Sosial dan Ilmu Politik UGM, 2006)
ABSTRACT A stress could happen to c'i'c'er'one'. A stress which is related to work is well known as a work stress. The 1110re SOMCOne ll'OlICS the 11101e stressors. (sources of stress) will he received. Its research is aimed at recognizing the correlation between work length and work stress on Librarian oailwary of Gatijah Mada University, The research uses a quantitative method with a questioner as a data collecting instrument. h is also a population research that takes total population 01 31 persons. Primary data is processed iolind out the work stress level. The outcome oldie research that has been already known is about 41.9 Yo respondents or 13 librarians got low work stress and 58,1 % respondents or 18 librarians don't got stress'. h CO/IS/s/s o1.7 11Wiland 6 woman ollihich 2 of them are from senior high school